2004
DOI: 10.1177/147323000403200513
|View full text |Cite
|
Sign up to set email alerts
|

Chronotropic Effect of the Antithrombotic Agent Cilostazol in a Patient with Sick Sinus Syndrome and Syncope

Abstract: In this case report we describe an 80-yearold man with sick sinus syndrome (SSS) who developed syncope attacks. The diagnosis of SSS was based on electrocardiographic evidence of markedly prolonged sinus arrests associated with syncope attacks while in hospital. The patient was given cilostazol, an antithrombotic agent that selectively inhibits cyclic nucleotide phosphodiesterase type 3, at a dose of 100 mg twice daily. The syncope attacks ceased, and an electrocardiogram obtained 1 week after the start of cil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…Therefore, cilostazol may serve as an effective cardioprotective drug, with its beneficial effects in preventing arrhythmia. Investigations on the effects of cilostazol on heart rate variability (HRV) have shown that cilostazol significantly improves a slow heart rate (34, 35). However, it is important to note that the evidence regarding cilostazol and tachyarrhythmia is still limited and unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, cilostazol may serve as an effective cardioprotective drug, with its beneficial effects in preventing arrhythmia. Investigations on the effects of cilostazol on heart rate variability (HRV) have shown that cilostazol significantly improves a slow heart rate (34, 35). However, it is important to note that the evidence regarding cilostazol and tachyarrhythmia is still limited and unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the heart rates of three patients increased after cilostazol use. Treatment with cilostazol was continued in Case 2 in anticipation of favorable chronotropic effects in patients with sinus bradycardia (18).…”
Section: Discussionmentioning
confidence: 99%
“…Cilostazol has positive chronotropic effects and has been used to treat human patients with bradyarrhythmias, such as atrioventricular (AV) block and SSS [2, 9, 10, 12, 15, 19]. Cilostazol has also been reported to have long-term chronotropic effects [5, 9].…”
mentioning
confidence: 99%
“…In this case, although the patient exhibited premature beats, atrial fibrillation was not observed. In human patients, cilostazol is used until PMI can be performed and in patients unable to receive a pacemaker [5, 9, 10]. …”
mentioning
confidence: 99%
See 1 more Smart Citation